THE EFFECT OF USING PODCAST TECHNOLOGY TO ENHANCE ENGLISH LISTENING COMPREHENSION - Ni Putu Ayu Bella Damayanti; Ni Nyoman Padmadewi; Luh Putu Artini (IKIP Siliwangi, 2024)
This study aims to investigate the effectiveness of using podcast technology to enhance English listening comprehension. The data were obtained by quantitative methods. A quasi-experimental method with pre-test and post-test experimental techniques. This study population involved sixty students in eighth-grade junior high school students in SMPN 1 Selemadeg Tabanan Bali. The population divided become two classes, thirty were students in the control group class, and thirty students were in the experimental group class. This researcher used purposive sampling. The control group class was taught by listening to the teacher, and the experimental group class was taught via podcast. In collecting data, this research used the listening test provided in the pre-test and post-test. To analyse data, the researchers implemented SPSS version 26 of the independent t-test to examine the significant difference in the scores between the control group and experimental group to enhance English listening comprehension. After giving the treatment by implementing podcasts, they revealed that podcasts enhance students' English listening comprehension skills.